Solubility of sulfacetamide in aqueous propylene glycol mixtures: Measurement, correlation, dissolution thermodynamics, preferential solvation and solute volumetric contribution at saturation (2019)
The equilibrium solubility at temperatures from (278.15 to 318.15) K, dissolution thermodynamics, preferential solvation, and apparent specific volume at saturation of sulfacetamide (SCM) in {propylene glycol (PG) (1) + water (2)} mixtures is reported. Mole fraction solubility of SCM (x3) increases when temperature arises and also increases with the PG proportion arising. Solubility behavior was adequately correlated and/or predicted by the Jouyban-Acree and Jouyban-Acree-van't Hoff models and the obtained mean percentage deviations (MPD) are varied between 6.5 and 11.5%. Apparent thermodynamic analysis of dissolution and mixing was performed in all the mixtures and neat solvents. Based on the inverse Kirkwood-Buff integrals (IKBI) is observed that SCM is preferentially solvated by water molecules in water-rich mixtures but preferentially solvated by PG in the other mixtures. Further, the apparent specific volumes of SCM at saturation were also calculated.